A atuação do professor de matemática na educação de jovens e adultos: conhecendo a problemática. - Migliorança, Fernanda (2004)
The Education of Young and Adults comes gaining space in the research carried through in the educational area. A great concern exists in understanding the process of education for which passes these people, who had remained many years without schooling or moved away from the educational system. An inquiry on the practical of the professors who act on the Education of Young and Adults is important to understand this process better, once that these professionals are responsible for the learning of this population and their insertion in the educative field. The particularity of this work is in investigating how the professor of Mathematics acts on the Education of Young and Adults, searching to know better their Mathematics perceptions and its teaching and also about learning of Mathematics for this population. For this, besides observing the teaching performance of these professionals it was looked to better know them through interviews and analysis of a study of case elaborated from participants of the inquiry classrooms events. The research had three professors of Mathematics participants, who act on the Education of Young and Adults in a state public school of a country city of São Paulo, and the students of one of its classrooms. Given the participants characteristics, the research constituted in three studies of case, each one referring to a professor and its classroom. To base this study I abandoned legal supports that sustain this modality of education, about profile of this clientele, about the situation of Mathematics education for these pupils and about basic and permanent formation of the professors who act on this area. Some results of the research are showed to follow. Young and adult people initiates their studies or returns to school after many years of removal with clear intentions: they search to invest in the study, since they had not access on it in the appropriate age, trying to improve their conditions of life. Moreover, they bring back specific and previous knowledge on the return to school, that assists or not themselves in learning process. All these aspects must be recognized and valued by the professors, searching to take care of young and adults' objectives that had made them return to school. When it has reported to the searched professors, it has evidenced that the lack of specific formation to teach Mathematics to young and adult people and the diffculties found in the work environment, in the school and its context, has important influences in pedagogical practical. However, when the professors have themselves availability to analyze their practical one, they invest in the diffculties overcoming and looking for new ways, even not finding institution support. For these professors, the idea of that teaching is a solitary passage becomes stronger. Although restricted, this educational scene of Mathematics teaching for young and adult people gives some suggestions to improve formation and performance of the professionals who act on this area.